Abnormal gastric adaptive relaxation in patients with gastrooesophageal reflux. Issue 5 (May 1990) - Hartley, M N; Walker, S J; Mackie, C R
Abstract : Gastric adaptive relaxation was measured in 15 healthy volunteers (control group) and in 12 patients with symptomatic gastrooesophageal reflux confirmed by 24 hour pH monitoring (reflux group). The control group were: 13 men, two women; median age 30 years, range 22-41; median body weight 70 kg, range 50-79 kg. All were asymptomatic on no medication. The reflux group were: eight men, four women, median age 48 years, range 23-65; median body weight 77 kg, range 60-92 kg. Medication was withheld for 12 hours before the study. Endoscopy showed no abnormality in five patients, oesophagitis in three patients and oesophagitis with hiatus hernia in four patients. Fasted subjects were intubated with a Ryle's tube containing a pressure microtransducer within a flaccid plastic bag (800 ml). Gastric corpus-fundus pressure was recorded during distension of the bag with 460 (20) ml mean (SD) of air over 30 seconds. Pressure indices (median: range) derived from areas under the pressure curves during distension were: control: 12.7 (7.5-17.1) cm H2O; reflux: 9.1 (6.4-13.3) cm H2O, p less than 0.01 (Mann Whitney U test). Similar results were obtained from pressure indices derived from recordings during the immediate postdistension period. No correlation was found between pressure indices and age, sex or body weight. The results indicate that the gastric pressure response to distension is reduced in patients with gastrooesophageal reflux.